2003
DOI: 10.1046/j.0905-6157.2003.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Total and allergen‐specific IgE levels in serum reflect blood eosinophilia and fractional exhaled nitric oxide concentrations but not pulmonary functions in allergic asthmatic children sensitized to house dust mites

Abstract: Although elevated levels of serum immunoglobulin E (IgE) are considered the hallmark of atopic diseases, their clinical value in evaluating subjects with allergic disorders is under debate. To evaluate possible relationships between serum IgE levels and a variety of clinical parameters, 83 mild asthmatic children [10.98-year-old (2.95)], sensitized to house dust mites (HDM) Dermatophagoides pteronyssinus (Dp) or D. farinae (Df), were enrolled. As compared with normal control reference values detected in our la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
7
31
0
Order By: Relevance
“…We also determined the relationship of serum factors to FeNO levels. In agreement with prior studies, [16][17][18][19]27 we found that there was a direct correlation of serum total IgE and ECP levels with FeNO levels in our cohort (Table I and Fig E3, A and B, in the Online Repository at www.jacionline.org). We also found a weak direct correlation between serum nitrate levels and FeNO levels (r 2 5 0.0083, P 5 .0499; Table I and Fig E3, C).…”
Section: Factors Associated With Variability Of Feno Levelssupporting
confidence: 93%
See 1 more Smart Citation
“…We also determined the relationship of serum factors to FeNO levels. In agreement with prior studies, [16][17][18][19]27 we found that there was a direct correlation of serum total IgE and ECP levels with FeNO levels in our cohort (Table I and Fig E3, A and B, in the Online Repository at www.jacionline.org). We also found a weak direct correlation between serum nitrate levels and FeNO levels (r 2 5 0.0083, P 5 .0499; Table I and Fig E3, C).…”
Section: Factors Associated With Variability Of Feno Levelssupporting
confidence: 93%
“…14,15 In patients with asthma and atopy, serum total and allergenspecific IgE levels, serum eosinophil cationic protein (ECP) levels, and peripheral blood eosinophils are all associated with increased FeNO levels. [16][17][18][19] In healthy adult subjects male sex, height, upper respiratory tract infection (URI), and nitrate intake have been associated with increased FeNO levels, [20][21][22][23][24][25][26][27] whereas cigarette smoking 28 and hypertension 29 have been associated with low FeNO levels. There are conflicting reports about whether age is associated with differences in FeNO levels in adults, 20,27 whereas in children there is more consensus that increasing age is associated with higher FeNO levels.…”
mentioning
confidence: 99%
“…Conversely, only very high eosinophil counts (>600 cells/mm 3 ) and an elevation of total serum IgE concentrations above 335 kU/L were strongly linked to high FeNO levels. Interestingly, among factors related to the patient history known to influence the natural course and/or the severity of asthma, only the presence of neonatal respiratory distress turned out to be a potential factor associated with low FeNO level in childhood atopic asthma (3,23).…”
Section: Discussionmentioning
confidence: 99%
“…Different authors have shown that FeNO levels are elevated in childhood allergic asthma and correlated with the degree of allergic sensitization and eosinophilic inflammation (1,3), whereas studies on associations with lung function parameters led to conflicting results. None of these studies explored the link between FeNO lev-els and allergic sensitization or eosinophilia on the basis of a multivariate analysis able to identify potential risk factors.…”
Section: Introductionmentioning
confidence: 97%
“…Early studies investigated eosinophilia as a potential biomarker [68][69][70][71][72]. One study showed variations in immune response within seemingly homogeneous IgE-mediated asthma phenotypes [73].…”
Section: Phenotypes To Asthma Endotypesmentioning
confidence: 99%